Post translational modifications of Rab GTPases. (4th March 2018) - Shinde, Swapnil Rohidas; Maddika, Subbareddy
ABSTRACT: Rab GTPases, the highly conserved members of Ras GTPase superfamily are central players in the vesicular trafficking. They are critically involved in intracellular trafficking pathway, beginning from formation of vesicles on donor membranes, defining trafficking specificity to facilitating vesicle docking on target membranes. Given the dynamic roles of Rabs during different stages of vesicular trafficking, mechanisms for their spatial and temporal regulation are crucial for normal cellular function. Regulation of Rab GTPase activity, localization and function has always been focused in and around the association of GDP dissociation inhibitor (GDI), Guanine nucleotide Exchange Factor (GEFs) and GTPase accelerating protein (GAP) to Rabs. However, several recent studies have highlighted the importance of different post-translational modifications in regulation of Rab activation and function. This review provides a summary of various post translational modifications (PTMs) and their significance to regulate localization and function of different Rabs.